RANCANG BANGUN PROTOTYPE SISTEM PENGENDALIAN KECEPATAN DAN PENGEREMAN MENGGUNAKAN SENSOR JARAK - Alimuddin Mappa; Markus Dwiyanto Tobi Sogen (Electro Luceat, 2019)
The research carried out aims to create an electric motor speed control and braking system that is used as a reference for electric car safety systems. By regulating the voltage received by a DC motor. This system uses Arduino UNO as a controller. To measure the distance of a car with a barrier using the Ping Parallax proximity sensor. Signal PWM (Pulse Width Modulation) from the microcontroller is used to regulate the speed of the DC motor as the main driver of the vehicle. Tests carried out using a miniature car with a track length of 2 (two) meters. The speed of a miniature electric car will stop before a collision occurs. braking uses the method of plugging by reversing the source polarity at distances below 10 (ten) cm, so that the motor will spin back to avoid the rest of the motor rotation that does not get a supply voltage. From this method, several motor conditions will be stopped gradually. Display distance between the vehicle with a barrier and motor rotation speed can be seen on the LCD